KK Dragway / Mohd Ridzuan Osman ... [et al.] - Osman, Mohd Ridzuan; Abd Rahman, Ag Juhari Rahman; Mohd Abidin, Mohd Hamizan; Albert, Hurdi (2011)
Our business purpose is introduce to public about drag sport and be the most efficiency maker to built a relationship between other racer and any fans of this sport. We also will provide a comfortable place to expose their interest in a right place.